The relationship between psychological stress and mindfulness among outstanding students in the school basic stage - A. A. Alazzam; A. A.K. Al-Shoqran; B. M. Suleiman; M. A. Rababah; B. M. Al-Hawamdeh; I. A.M. Al-Maraziq; I. Tanjour; F. A.M. Al-Habies (Образование и наука)
Introduction. Outstanding students frequently experience psychological stress in many facets of their lives, which impedes their capacity for self-expression, self-control, and problem-solving. It negatively impacts both their physical and mental health in several ways. On the other hand, it has been discovered that mindfulness practices improve physical and sensory well-being and help with stress and anxiety management.Aim. The present research aimed to find out how much psychological stress outstanding students at the primary stage experienced and how that stress is related to mindfulness.Methodology and research methods. A total of 232 kids between the ages of 10 and 14 were involved in the study; they were specifically chosen based on their academic records. Students have to meet the selection requirements with grades higher than 90% in every subject. A questionnaire including a 50- item psychological stress measure with three-point Likert ratings and a mindfulness scale was used to collect data.Results. According to the research outcomes, outstanding students had high levels of mindfulness and low levels of psychological stress. There is a negative correlation between psychological stress and mindfulness. Additionally, there were no appreciable gender differences in the study measures of mindfulness or psychological stress.Scientific novelty. Based on the study findings, psychological stress negatively affects outstanding students’ physical and mental health and surges their levels of fatigue, tension, and poor focus. It also underlined how psychological stress is detrimental to the students’ psychological health. Accordingly, it is recommended to practise mindfulness as a helpful tactic for managing students’ psychological stress and keeping students from feeling overburdened. Achieving mental health is vital for students in all domains of their lives.Practical significance. The study provides valuable insights and practical recommendations for stakeholders. It suggests the development of psychological and educational counselling programmes that incorporate mindfulness strategies for outstanding students. It also emphasises the need for proactive planning and the implementation of strategies to mitigate psychological stress in students while addressing their developmental and curative needs. The study results can assist researchers and educators in designing educational and counselling programmes catering to outstanding students’ psychological, social and educational needs. Furthermore, the results can help teachers understand the intricate relationship between mindfulness and psychological stress. Specifically, cultivating acceptance as an attitude can directly contribute to reducing psychological stress, making it essential for teachers to guide students in practising mindfulness as a stress management tool.